2016
DOI: 10.3389/fpls.2016.01805
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Sequences of Xanthomonas euvesicatoria Strains Clarify Taxonomy and Reveal a Stepwise Erosion of Type 3 Effectors

Abstract: Multiple species of Xanthomonas cause bacterial spot of tomato (BST) and pepper. We sequenced five Xanthomonas euvesicatoria strains isolated from three continents (Africa, Asia, and South America) to provide a set of representative genomes with temporal and geographic diversity. LMG strains 667, 905, 909, and 933 were pathogenic on tomato and pepper, except LMG 918 elicited a hypersensitive reaction (HR) on tomato. Furthermore, LMG 667, 909, and 918 elicited a HR on Early Cal Wonder 30R containing Bs3. We exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
49
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 37 publications
3
49
0
Order By: Relevance
“…Both species form sister lineages within the larger X. euvesicatoria species complex, as initially described by Parkinson et al . () and consists of a heterogeneous group of bacteria that share ≥98% average nucleotide identities (Barak et al ., ; Constantin et al ., ; Bansal et al ., ). Being a seed‐borne pathogen, introduction of contaminated transplants into fields is considered a primary source of Xanthomonas inoculum (Abrahamian et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Both species form sister lineages within the larger X. euvesicatoria species complex, as initially described by Parkinson et al . () and consists of a heterogeneous group of bacteria that share ≥98% average nucleotide identities (Barak et al ., ; Constantin et al ., ; Bansal et al ., ). Being a seed‐borne pathogen, introduction of contaminated transplants into fields is considered a primary source of Xanthomonas inoculum (Abrahamian et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have found atypical bacterial spot strains in Europe, Asia, and Africa (34)(35)(36). The genomes of two of these strains have been sequenced previously: X. perforans strain 4P1S2, from Italy, and X. euvesicatoria strain LMG918, from India (36,37). Preliminary analysis of the genome of strain 4P1S2 showed that it contained regions that were identical in sequence to regions of genomes of other Xanthomonas species, suggesting recombination (34).…”
mentioning
confidence: 94%
“…Preliminary analysis of the genome of strain 4P1S2 showed that it contained regions that were identical in sequence to regions of genomes of other Xanthomonas species, suggesting recombination (34). Strain LMG918 was identified as X. euvesicatoria but is amylolytic, which is not typical of X. euvesicatoria strains, and sequencing of its genome revealed unique effector gene content relative to other X. euvesicatoria strains (37). Together with our initial analysis of the strains from Nigeria, these findings suggest that there are genetic groups of X. euvesicatoria and X. perforans that are not represented in genome studies of U.S. strains.…”
mentioning
confidence: 99%
“…However, these aforementioned tools have significant limitations because they examine only a subset of the bacterial genome of interest and thus restrict molecular epidemiological analyses (12). For instance, virulence-or effector-based typing can be misleading when used to infer ancestry, due to the loss and acquisition of virulence genes (17,18).…”
mentioning
confidence: 99%